Phytotoxic Activity of Bioactive Compounds from Four Plants against Selected Weeds in Agriculture - Tauseef Anwar; Huma Qureshi (Acta Scientiarum Polonorum. Formatio Circumiectus)
Aim of the study: Heavy doses of synthetic weed control chemicals have caused herbicide resistance in weeds. Natural compounds produced by living organisms constitute a wide field for ecologically safe herbicides. The current investigation was directed to test allelopathic potential of hexane extracts of selected plants against common weeds of agriculture.